Vulval epidermoid cysts - Di Prima, T... (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 1993)
Epidermal cysts are benign neoplasms appearing in the skin and are surrounded by an epithelial wall which is similar to the superficial epithelium. They are most frequently located on the face, trunk, extremities and on the scalp, while they are very rare on the vulva. A case of epidermoid cysts on labia majora in a 47-year-old patient is described.
Keywords: Epidermal cyst; Pathology; Vulvar diseases